2008
DOI: 10.1128/mcb.00709-07
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP (cAMP)-Mediated Stimulation of Adipocyte Differentiation Requires the Synergistic Action of Epac- and cAMP-Dependent Protein Kinase-Dependent Processes

Abstract: Cyclic AMP (cAMP)-dependent processes are pivotal during the early stages of adipocyte differentiation. We show that exchange protein directly activated by cAMP (Epac), which functions as a guanine nucleotide exchange factor for the Ras-like GTPases Rap1 and Rap2, was required for cAMP-dependent stimulation of adipocyte differentiation. Epac, working via Rap, acted synergistically with cAMP-dependent protein kinase (protein kinase A [PKA]) to promote adipogenesis. The major role of PKA was to down-regulate Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
131
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 73 publications
11
131
2
1
Order By: Relevance
“…We observed the same We have recently shown that the adipogenic effect of elevated cAMP levels relies on the activation of both protein kinase A (PKA) and the exchange protein activated by cAMP (Epac). 28 Using selective activators of both PKA and Epac, we show that only the PKA activator augmented expression of C/EBPd ( Figure 3d). …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…We observed the same We have recently shown that the adipogenic effect of elevated cAMP levels relies on the activation of both protein kinase A (PKA) and the exchange protein activated by cAMP (Epac). 28 Using selective activators of both PKA and Epac, we show that only the PKA activator augmented expression of C/EBPd ( Figure 3d). …”
Section: Resultsmentioning
confidence: 86%
“…In fact, it is the mitogen-activated protein kinase (MAPK) that is responsible for CREB phosphorylation during the initiation of adipocyte differentiation. 28 An important function of PKA during adipose conversion is inhibition of the Rho kinase 28 that in turn can inhibit adipogenesis by blocking the MAPK-mediated phosphorylation of CREB. 31 To ensure that the failure to induce C/EBPd in the absence of Mdm2 was not a result of uncontrolled Rho-kinase activity, we concomitantly treated the p53 À/À ;mdm2 À/À MEFs with IBMX and increasing doses of a Rho-kinase inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Both IBMX and dexamethasone trigger the activation of protein kinase A by increasing the intracellular concentration of cAMP, thereby promoting adipocyte differentiation 36 . The major role of protein kinase A in adipogenesis has been thought to lie in downregulation of RhoA and ROCK activity 37 . In the present study, we found that Rho activity is rapidly reduced after treatment of DFAT cells with the adipogenic cocktail, and the downregulation of RhoA-ROCK signalling then promotes adipocyte differentiation via modulation of remodelling of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is prompted by the observation that TLR4 expression is induced in the liver by hepatocyte-specifi c NS5A expression [ 28 ]. As endotoxin-TLR4 pathway is established in the pathogenesis of ALD [ 29 , 30 ], a synergism between alcohol-mediated endotoxemia and NS5A-induced TLR4 overexpression was predicted.…”
Section: Ectopic Tlr4 Activation Underlies Hcv-alcohol Synergismmentioning
confidence: 99%